2019
DOI: 10.1186/s13063-019-3778-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for insomnia (CBTi) as a treatment for tinnitus-related insomnia: protocol for a randomised controlled trial

Abstract: BackgroundA significant proportion of patients with chronic tinnitus report clinical levels of sleep disturbance (insomnia). Despite the significant health and functioning implications of this, no rigorous trials have investigated treatments that target tinnitus-related insomnia. This is the first randomised controlled trial evaluating Cognitive Behavioural Therapy for insomnia (CBTi) in tinnitus compared with other psychological treatments.Methods/designThe study will test the efficacy of group CBTi as a trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Second, during the COVID-19 epidemic, medical staff with physical diseases may worry about infection, resulting in more serious symptoms of anxiety and insomnia. Moreover, negative thoughts about threatening symptoms may lead to persistent insomnia (36). Another important finding of this study was that all the dimensions and total score of psychological resilience were significantly negatively correlated with the ISI total score.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Second, during the COVID-19 epidemic, medical staff with physical diseases may worry about infection, resulting in more serious symptoms of anxiety and insomnia. Moreover, negative thoughts about threatening symptoms may lead to persistent insomnia (36). Another important finding of this study was that all the dimensions and total score of psychological resilience were significantly negatively correlated with the ISI total score.…”
Section: Discussionmentioning
confidence: 56%
“…Second, during the COVID-19 epidemic, medical staff with physical diseases may worry about infection, resulting in more serious symptoms of anxiety and insomnia. Moreover, negative thoughts about threatening symptoms may lead to persistent insomnia ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…CBT-I in the short term has the same effect as drug therapy on insomnia. Since the drug treatments pose long-term side effects in people with insomnia, the desire to treat with CBT has increased [14,15]. A meta-analysis study by Geiger-Brown et al (2015) found that sleep quality improves after the CBT-I treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There is robust evidence available suggesting that specific types of cognitive behavioral therapy (CBT) can be effective in treating tinnitus and insomnia (Cima et al 2012;Geiger-Brown et al 2015;Martinez-Devesa et al 2010; for a review see McKenna & Daniel 2006), as well as anxiety and depression disorders (Carpenter et al 2018;Twomey et al 2015). Current trials suggest that CBT is an effective intervention for the management of tinnitus-related insomnia (Andersson et al 2005;Beukes et al 2017;Jasper et al 2014;Marks et al 2019;Weise et al 2016). However, it is not clear whether CI users would be willing to undergo new therapies to treat their tinnitus-related sleep problems in addition to the therapies they may already receive to manage any adverse effects associated with their profound hearing loss.…”
Section: Implications For Clinical Managementmentioning
confidence: 99%